Does Gen Z’s gender moderate the effect of celebrity–brand–audience congruence on purchase intent? A case study from Pakistan - Arif, Abdur Rehman; Tat, Huam Hon; Hafeez, Muhammad; Rehman, Sana ur; Mat Saad, Norizan; Ahmad Nasir, Waqar (Routledge, 2026)
This study examines the impression of the congruence between celebrity and brand as well as their alignment with the target audience, and the likelihood of the Z Generation to purchase a product. The study also examines the moderation of gender of target audience. Using quota sampling, the study analyzed data through survey based empirical research from 384 responses. Path, mediation, and moderation analysis is done to assess the associations of constructs through SMART-PLS. The results specify that when a celebrity endorsement aligns with a brand, it has a positive impact on the Z Generation’s propensity to purchase in Pakistan. Furthermore, when the celebrity’s image is aligned with target audience, it increases the effectiveness of celebrity endorsements. Importantly, Gen Z consumers of all sexes seem to assess congruent marketing stimuli similarly, giving alignment and authenticity precedence over gendered viewpoints. It recommends that marketers switch from demographic targeting to congruence and psychographic-based tactics that appeal to Gen Zers of all genders equally. The study findings can be useful for firms aiming to optimize their marketing influence to meticulously choose celebrities whose image aligns with both their brand identity and the target consumers.